Combination of molecular and traditional approaches to identify ice-ice disease causing bacteria on the seaweed Kappaphycus alvarezii (Doty) - Tran, Thi Hong Ha; Le, Mai Huong; Nguyen, Dinh Luyen; Hoang, Kim Chi; Tran, Thi Nhu Hang; Tran, Mai Duc; Tran, Phuc Lam; Le, Huu Cuong (Vietnam Journal of Marine Science and Technology, 2025)
The main cause of the disease is that bacteria thrive and attack seaweed by secreting carrageenan hydrolyzing enzyme, making it more vulnerable to other microbial pathogens. In this study, the bacterial composition of healthy and ice-ice samples of Kappaphycus alvarezii were analyzed by sequencing one hundred 16S rRNA gene of random clones from relevant gene libraries. In addition, the conventional method was used to isolate bacteria from the ice-ice disease seaweed and identify carrageenan hydrolyzing bacteria. Our results displayed a significant difference in the number of bacterial operational taxonomic units (OTUs) between the healthy (11 OTUs) and disease samples (31 OTUs). Bacterial composition in the healthy algal samples was dominated by two genera Cobetia and Roseobacter, which accouted for 39% and 21% of the total, respectively. In contrast, the ice-ice disease algal sample was dominated by the genera Pseudoalteromonas and Phaeobacter, which accouted for 14% and 12% respectively, closely followed by three genera Alteromonas, Salinimonas and Psychrobacter. After screening bacterial isolates from the ice-ice disease sample for carrageenan, two types of isolates were visually observed to produce this enzyme, indicated by a clear halo zone on 0.5% carrageenan agar plate. Two carrageenan-producing isolates were subsequently identified and named as Alteromonas sp. IKS 3 and Tenacibaculum sp. IKS4. In the pathogeny test, at 5 × 104 CFU/mL, the isolates IKS3 and IKS4 caused an ice-ice disease syndrome to 75.33% and 59.66% K. alvarezii seaweed respectively, higher than that of the control (22%, without any isolate infection), indicating that Alteromonas sp. IKS3 and Tenacibaculum sp. IKS4 was an ice-ice disease that caused bacteria on the K. alvarezii seaweed.